A stable and easily regenerable solid amine adsorbent derived from a polyethylenimine-impregnated dialdehyde-cellulose/graphene-oxide composite. (22nd March 2022) - Qiu, Xianyu; Wang, Xiaoqiong; Chen, Shuixia
Abstract : A DAC-GO composite adsorbent with high CO2 adsorption capacity and low regeneration energy consumption was prepared through oxidation-gelation and crosslinking-amination. Abstract : Thermal stability and conductivity are important for long-term performance and easy regeneration of CO2 adsorbents. In this paper, a kind of dialdehyde-cellulose/graphene-oxide composite gel (DAC-GO) with a flexible structure was obtained successfully via periodate oxidation and a self-assembly method. Polyethyleneimine (PEI) was impregnated and crosslinked into a DAC-GO gel using ethylene glycol diglycidyl ether (EGDE) to prepare a solid amine adsorbent (DAC-GO-cPEI) for CO2 adsorption. The adsorption amount and regeneration performance of the DAC-GO-cPEI were evaluated in comparison with those of the adsorbents prepared without adding GO (DAC-cPEI) or crosslinking (DAC-GO@PEI). The structure of the composite gels was different from that of the initial DAC gel, accompanied by the trend of an initial increase in the adsorption amount followed by a decrease as the amount of GO increased. Among DAC-GOs, the DAC-0.05GO with a leaf-vein-branched structure exhibited a higher adsorption amount than others after being functionalized with PEI, in which DAC-0.05GO-cPEI was suitable for achieving long-term adsorption performance. Under wet conditions, DAC-0.05GO-cPEI reached a CO2 adsorption amount as high as 4.25 mmol g −1 at 25 °C, and could be regenerated by purging with a flow of N2 at a low temperature of 70 °C. Furthermore, DAC-0.05GO-cPEI maintained a stable adsorption amount of more than 4 mmol g −1 after 12 adsorption–desorption cycles, demonstrating that DAC-0.05GO-cPEI was an effective CO2 adsorbent with long-term performance.